MENINGKATKAN MINAT MEMBACA MELALUI IMPLEMENTASI PROSEDUR MEMBACA TERBIMBING (GUIDED READING PROCEDURE) - mulyadi . (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2019)
Reading is one of the activities out in the learning process. Reading is also an ongoing communication skill. After the researchers used the implementation of the guiding reading approach (Guilded Reading Procedure) students’ interest in reading had increased very well with an average value of 88.6. This research used action research as much as 2 cycles. Clycle I consisted of 6 stages: Plannging, observation, questionnaire, interview, reflection and revision. While the second cycle consists consisted of 6 stages: Plannging, observation, questionnaire, interview and reflection. The target of study is students of class III A MIN 3 Langsa City. The conclusion of study was learning to read trought the implementation of reading procedure guide can have a positive influence on learning outcomes and can increase student motivation in reading.